A novel printed slow-wave microwave - Ong, Sheng Jie. (2010)
A circular helix has been a popular slow-wave structure but it cannot be fabricated using printed-circuit techniques. In this project, it is proposed to investigate a new type of slow-wave microwave structure which can be fabricated using printed-circuit techniques and which emulates the features of a circular helix. A planar waveguide structure, with slow-wave properties similar to those of a circular helix, confined planar helix is being investigated. It can be fabricated using printed-circuit techniques.